(3GdeMGSHI GdeJhSWI (B:s (3eONd fXQj JWHjbj (B/s - (3GdOgQGhj, ceGd GdOjfs; (3gdGd, YHO Gddg s ((3GdGScfOQjI(B: s (3OGQ GdeYQaI GdLGeYjI(B, s, 2000)
(3GdGWGQ GdeaGgjej ddeMGSHI hGdbhGFe GdeGdjI(B-(3bGFeI GdONd hbGFeI GdCQHGM GdeMJLRI(B-(3GdejRGfjI GdYehejI(B-(3bGFeI GdJOabGJ GdfbOjI(B-(3GdfbOjI hGdGSJKeGQGJ bUjQI GdCLd(B-(3GdeOfjjf hChQGb GdbHV(B-(3LQO hJbjje GdeNRhf GdSdYj(B-(3GdGjQGOGJ heTGcd GdGYJQGa HgG(B-(3GdGYJQGa HGdGjQGOGJ NdGd GdGfJGL YbhO GdebGhdGJ WhjdIs
Keywords: (3GdGSJKeGQs; (3GdeMGSHIs; (3GdfbhOs